2019
DOI: 10.1007/s11090-019-10000-1
|View full text |Cite
|
Sign up to set email alerts
|

Cell Repellent Coatings on Inner Walls of Tubes by Means of Transporting Discharge in Atmospheric Pressure

Abstract: We report a method to obtain biocompatible PEG copolymer coatings inside High Density Polyethylene (HDPE) and Pyrex tubes, which was successfully developed by using a transporting discharge. The latter being a dry process, it is easier to apply as compared to the conventional multistep wet chemical techniques. The results presented in this paper show that for a 70 cm tube good cell repellent properties as compared to the control was obtained for the entire length of the tube. The best nonfouling properties wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…PEG‐coated high‐density polyethylene and Pyrex tubes, developed via transport discharge in atmospheric plasma, have shown excellent antifouling properties with respect to CT‐26 (colon cancer). [ 72 ] Recently, Stahel et al [73] have demonstrated that atmospheric‐pressure plasma‐polymerized polyoxazoline coatings show remarkable promise as a new class of antibiofouling, biocompatible polymers for biomedical applications. Difficult to synthesize by conventional methods, plasma deposition of 2‐methyl‐2‐oxazoline‐based coatings in nitrogen atmospheric‐pressure DBD has proved to be a successful route toward synthesizing these films.…”
Section: Antibiofouling Self‐decontaminating and Biomimetic Surfacesmentioning
confidence: 99%
“…PEG‐coated high‐density polyethylene and Pyrex tubes, developed via transport discharge in atmospheric plasma, have shown excellent antifouling properties with respect to CT‐26 (colon cancer). [ 72 ] Recently, Stahel et al [73] have demonstrated that atmospheric‐pressure plasma‐polymerized polyoxazoline coatings show remarkable promise as a new class of antibiofouling, biocompatible polymers for biomedical applications. Difficult to synthesize by conventional methods, plasma deposition of 2‐methyl‐2‐oxazoline‐based coatings in nitrogen atmospheric‐pressure DBD has proved to be a successful route toward synthesizing these films.…”
Section: Antibiofouling Self‐decontaminating and Biomimetic Surfacesmentioning
confidence: 99%